Antiphotoaging effects of a group of antioxidant peptides through downregulating matrix metalloproteinases and inflammation factors - Huang, Yichao; Song, Juxingsi; Wang, Zhengbang; Zhu, Shaoqian; Hu, Yanan; Gan, Xinyue; Luo, Sai; He, Qian; Zhang, Liming; Wang, Qianqian (Frontiers in Cell and Developmental Biology, 2025)
Excessive ultraviolet B (UVB) exposure is the leading environmental contributor to the development of skin aging, also referred to as photoaging. We previously obtained a group of modified antioxidant peptides (WP5, LW5 and YY6), which were derived from marine organisms, through a single amino acid substitution, and demonstrated that the antioxidant peptides exhibited apparent protective effects against UVB-induced oxidative damage in human keratinocyte cells. Nonetheless, it remains uncertain whether they can alleviate skin photoaging caused by UVB. This research aims to investigate the anti-photoaging effects of the antioxidant peptides in vitro and in vivo and the underlying molecular mechanisms. We found that the antioxidant peptides significantly alleviated the senescence of HDF-a cells induced by UVB and suppressed the expression of matrix metalloproteinases (MMPs) and the degradation of collagen I, and the mitogen-activated protein kinase (MAPK) pathways, particularly the p38 MAPK pathway, might involve in anti-photoaging effects of the antioxidant peptides in HDF-a cells. Furthermore, an emulsion containing antioxidant peptides was prepared, and it was also found to inhibit the expression of MMPs and inflammation factors IL-6 and IL-1β in the mice exposed to UVB. Our results suggest that these antioxidant peptides might be applied as effective components in cosmetics for retarding skin photoaging in the future.